Enabling good relationships with young people: keeping Scotland's promise - David Woodier (Scottish Journal of Residential Child Care)
Scotland’s Independent Care Review made an unwavering commitment to en-suring the care experienced community would be at its very heart. The review concluded that the primary purpose of the care system needed to shift from protecting from harm to protecting all safe, loving, and respectful relation-ships. This shift puts the responsibility of change fairly and squarely on the shoulders of the workforce who care for young people. Supporting meaningful relationships with professionals in the lives of young people requires new ways of working. This article explores a central, but often overlooked, question: How do we ensure a relationship is good for a young person? The writer, with over thirty years’ experience, reflects on how trust and the capacity to love can be enabled when the workforce has time to focus and reflect on relationships. Practical ways individuals, working as part of a team, can engage more in-sightfully and empathetically with young people are discussed.